Facial Dermatoses Associated With Mask-Wearing in the COVID-19 Era: A Nationwide, Cross-Sectional, Multicenter, Questionnaire-based Study - Choi, Myoung Eun; Lee, Woo Jin; Ko, Joo Yeon; Kim, Kwang Joong; Kim, Jung Eun; Kim, Hei Sung; Park, Kui Young; Park, Mi Youn; Suh, Dae Hun; Shin, Kihyuk; Shin, Min Kyung; Ahn, Hyo Hyun; et al. (Annals of dermatology, 2024)
Daily usage of facial masks during coronavirus disease 2019 pandemic influenced on facial dermatoses. This study investigated the impact of mask-wearing habits on facial dermatoses. A nationwide, observational, questionnaire-based survey was conducted from July through August 2021, involving 20 hospitals in Korea. Among 1,958 facial dermatoses, 75.9% of patients experienced aggravation or development of new-onset facial dermatoses after wearing masks. In aggravated or newly developed acne patients (543 out of 743), associated factors were healthcare provider, female gender, and a long duration of mask-wearing. Irritating symptoms, xerosis, and hyperpigmentation were more frequently observed in this group. Aggravated or newly developed rosacea patients (515 out of 660) were likely to be female, young, and have a long duration of mask-wearing per day. Seborrheic dermatitis patients who experienced aggravation or development (132 out of 184) were younger, and they more frequently involved the chin and jaw in addition to the nasolabial folds and both cheeks. Contact dermatitis patients (132 out of 147) with aggravation or development tended to be female, involve both cheeks, and complain of pruritus. Aggravated or newly developed atopic dermatitis patients (165 out of 224) were more likely to be female, and had a higher baseline investigator global assessment score before mask-wearing. Clinical features and factors related to aggravation were different according to the types of facial dermatoses.